96.4k views
3 votes
-4h - 6 + 15 = 17 ( I don’t understand the concept.)

2 Answers

0 votes

Answer:

it is an algebraic expression (answer is h = -2 )

Simplify the expression

−4h−6 + 15 = 17

(Combine Like Terms)

(−4h)+(−6+15)=17

−4h + 9 = 17

Step 2: Subtract 9 from both sides.

−4h + 9 − 9 = 17 − 9

−4h=8

Step 3: Divide both sides by -4.


(-4h)/(-4) =
(8)/(-4)

h = -2

Explanation:

User Pranjal Doshi
by
5.0k points
6 votes

the concept is to find the value of h

-4h - 6 + 15 = 17 ( I don’t understand the concept.)-example-1
User Greg Hilston
by
5.2k points